Meningkatkan Hasil Belajar Siswa Melalui Metode Role Playing pada Mata Pelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) di Kelas V Sekolah Dasar - Rina Umaya; Muhammad Sarlin; Samsi Pomalingo (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This research aims to improve the learning outcomes of fifth grade elementary school students in Natural and Social Sciences (IPAS) subjects through the application of the Role Playing method. The Role Playing method was chosen because it is considered effective in improving students' conceptual understanding and critical thinking skills, as well as motivating students to actively participate in the learning process. This research uses an experimental method with a quasi-experimental pretest-posttest control group design. The research sample consisted of two fifth classes in an elementary school, namely an experimental class taught using the Role Playing method and a control class taught using conventional methods. Data was collected through student learning outcomes tests before and after treatment. Data were analyzed using the t-test to compare the differences in average learning outcomes between the experimental class and the control class. The research results showed that there was a significant difference between the learning outcomes of experimental class and control class students after the Role Playing method was applied. The average learning outcomes of experimental class students increased significantly compared to the control class. In conclusion, the Role Playing method is effective in improving the learning outcomes of fifth grade elementary school students in science and science subjects. This research recommends that teachers can apply the Role Playing method in science learning to increase students' understanding and interest in learning.